Sustainable nitrogen-doped functionalized graphene nanosheets for visible-light-induced photocatalytic water splitting. Issue 51 (21st May 2020) - Das, Gouri Sankar; Bhatnagar, Amit; Yli-Pirilä, Pasi; Tripathi, Kumud Malika; Kim, TaeYoung
Abstract : Nitrogen-doped graphene with surface functionalities enables highly efficient photocatalytic water splitting under visible light irradiation with excellent stability. Abstract : Nitrogen-doped functionalized graphene nanosheets (N-fGNS) were synthesized by a simple and green method and used for the visible-light-driven water splitting. Under visible light irradiation, N-fGNS produced H2 and O2 (1380 and 689 μM g −1 h −1, respectively) efficiently without co-catalysts. The excellent photocatalytic water splitting performance of N-fGNS is attributed to nitrogen doping and abundant surface defects as active sites.